PENTINGNYA POLA HIDUP BERSIH DAN SEHAT UNTUK ANAK DI DESA SENEMBAH - Dalimawaty Kadir; Beta Rapita Silalahi; Elia Putri; Juli Yanti Harahap; Siti Nur'ibni Aulia Hutagalung; Lesiana; Nadiah Azlila (LPPI UMN AL WASHLIYAH, 2026)
This community service initiative aims to enhance knowledge and awareness regarding the importance of a clean and healthy lifestyle, which is a crucial factor in improving health outcomes. Adopting such a lifestyle offers a greater chance of healthy growth, protection against various infectious diseases, and an improved quality of life. The issue faced by the partner community was a lack of awareness concerning the importance of clean and healthy living practices. The implementation employed a participatory approach involving stages of outreach, education, mentoring, and evaluation. The results indicate an increase in participants' knowledge and awareness regarding the importance of a clean and healthy lifestyle—specifically concerning personal and environmental hygiene, the consumption of nutritious food, the use of clean water, and the habit of washing hands before meals and after activities. This activity has made a positive contribution to fostering healthy living habits and supporting efforts to improve public health in Senembah Village.